The effect of intracoronary infusion of bone marrow-derived mononuclear cells on all-cause mortality in acute myocardial infarction: rationale and design of the BAMI trial - Mathur, Anthony; Arnold, Roman; Assmus, Birgit; Bartunek, Jozef; Belmans, Ann; Bönig, Halvard; Crea, Filippo; Dimmeler, Stefanie; Dowlut, Sheik; Fernández-Avilés, Francisco; Galiñanes, Manuel; Garcia-Dorado, David; et al. (European journal of heart failure, 2017)
Over the past 13 years bone marrow-derived mononuclear cells (BM-MNCs) have been widely investigated for clinical efficacy in patients following acute myocardial infarction (AMI). These early phase II trials have used various surrogate markers to judge efficacy and, although promising, the results have been inconsistent. The phase III BAMI trial has therefore been designed to demonstrate that intracoronary infusion of BM-MNCs is safe and will significantly reduce the time to first occurrence of all-cause death in patients with reduced left ventricular ejection fraction after successful reperfusion for ST-elevation AMI (powered with the aim of detecting a 25% reduction in all-cause mortality). This is a multinational, multicentre, randomized, open-label, controlled, parallel-group phase III study aiming to enrol approximately 3000 patients in 11 European countries with at least 17 sites. Eligible patients who have impaired left ventricular ejection (≤45%) following successful reperfusion for AMI will be randomized to treatment or control group in a 1:1 ratio. The treatment group will receive intracoronary infusion of BM-MNCs 2-8 days after successful reperfusion for AMI added on top of optimal standard of care. The control group will receive optimal standard of care. The primary endpoint is time from randomization to all-cause death. The BAMI trial is pivotal and the largest trial to date of BM-MNCs in patients with impaired left ventricular function following AMI. The aim of the trial is to provide a definitive answer as to whether BM-MNCs reduce all-cause mortality in this group of patients.
Keywords: echokardiografie; Cardiac regeneration; Europe; Female; Cause of Death; výsledek terapie; ženské pohlaví; Bone marrow-derived mononuclear cells; funkce levé komory srdeční; ST Elevation Myocardial Infarction; lidé; Evropa; infarkt myokardu s elevacemi ST úseků; BAMI; Treatment Outcome; Cell therapy; míra přežití; Echocardiography; transplantace kostní dřeně; Male; Myocardial infarction; Heart failure; Survival Rate; Bone Marrow Transplantation; mužské pohlaví; příčina smrti; Cardiovascular disease; Ventricular Function, Left; Humans